High mobility solution-processed C8-BTBT organic thin-film transistors via UV-ozone interface modification. Issue 40 (9th October 2017) - Wei, Weiyao; Yang, Cheng; Mai, Jiaying; Gong, Yanfen; Yan, Longsen; Zhao, Kai; Ning, Honglong; Wu, Sujuan; Gao, Jinwei; Gao, Xingsen; Zhou, Guofu; Lu, Xubing; et al.
Abstract : UV-ozone exposure directly on the dielectric surface to get an OTFT mobility as high as 6.50 cm 2 (V s) −1 . Abstract : The interface between the dielectric and the active layer plays a critical role on the performance of solution-processed organic thin-film transistors (OTFTs). However, the creation of a high quality interface still represents a considerable challenge because it requires the balancing of surface energy with surface wettability. This study shows that UV-ozone treatment is very effective to obtain a high quality interface between a dielectric SiO2 film and a solution-processed 2, 7-dioctyl[1]benzothieno[3, 2- b ][1]benzothiophene (C8 -BTBT) semiconductor film. After only one minute UV-ozone exposure on the SiO2 surface, the hole mobility at room temperature reaches 6.50 cm 2 (V s) −1 for a solution-processed C8 -BTBT-OTFT. UV-ozone treatment can not only modify both surface energy and surface wettability but also clean the SiO2 surface. Consequently, it changes the degree of ordered growth, grain sizes, and grain boundaries in C8 -BTBT films. Hence, UV-ozone treatment is a simple and efficient way to produce the desirable interface qualities that enable the highly ordered growth of C8 -BTBT films. Using this method it is also very promising to produce a high-quality interface between the dielectric film and other solution-processed organic semiconductors to fabricate other high-performance OTFT applications.